Assessment of Ultra-Early Administration of Sacubitril Valsartan to Improve Cardiac Remodeling in Patients With Acute Myocardial Infarction Following Primary PCI: Rational and Design of a Prospective, Multicenter, Randomized Controlled Trial - Li, Zhengwei; Fu, Guosheng (Frontiers in physiology, 2022)
Despite coronary re-vascularization, the common complications of acute myocardial infarction (AMI), cardiac remodeling, and heart failure (HF), is increasing globally. Sacubitril valsartan (SV), an angiotensin receptor-neprilysin inhibitor (ARNI), has been previously demonstrated to improve HF. We further hypothesize that ultra-early SV treatment is also effective in preventing cardiac remodeling for patients with AMI following primary percutaneous coronary intervention (PCI). The Assessment of ultra-early administration of Sacubitril Valsartan to improve cardiac remodeling in patients with Acute Myocardial Infarction following primary PCI (ASV-AMI) trial is a prospective, multicenter, randomized controlled trial in China planning to enroll at least 1,942 eligible patients from 10 centers. After successful primary PCI of culprit artery within 24 h, AMI patients are randomized to 2 h group or 3-7 days group with SV treatment. The major endpoints are echocardiographic measurement, cardiothoracic ratio, and N-Terminal pro-B-Type Natriuretic Peptide (NT pro-BNP) at baseline, 1, 3, 6, and 12 months. The secondary endpoints included MACE (cardiac arrest, cardiogenic death, myocardial infarction, and target vessel re-vascularization), in-/out-patient HF, EuroQol Five Dimensions Questionnaire (EQ-5D), and Kansas City Cardiomyopathy Questionnaire (KCCQ). The ASV-AMI trial is the first clinical trial of ultra-early administration of SV in the treatment of post-PCI AMI, adding more clinical evidence. Early application of SV to prevent cardiac remodeling in AMI patient is a major focus of this trial. Trial registration Chinese Clinical Trial Registry (http://www.chictr.org.cn; ChiCTR2100051979). Registered on 11 October 2021.